Incompressible Limit for the Compressible Flows of Nematic Liquid Crystals in the Whole Space - Young-Sam Kwon (Advances in Mathematical Physics)
We consider the compressible flows of liquid crystals arising in a variety of scientific examples. We here study the incompressible limit of weak solutions of the compressible flows of nematic liquid crystals in the whole space R2.